1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Nonlinear 2nd order ode reduction solutions

  1. Mar 30, 2012 #1
    hey guys

    i've been trying to work out this ode reduction question,

    http://img204.imageshack.us/img204/8198/asdawt.jpg [Broken]

    after i use the hint and end up with a seperable equation then integrate to get

    & p=\pm \frac{1}{\sqrt{{{y}^{2}}-2c}} \\
    & \text{Then}\,\,\,\text{integrating}\,\,\,\text{again (using}\,\,wolframalpha) \\
    & y=\pm \log \left( \sqrt{{{y}^{2}}-2c}+y \right)+c \\
    & A{{e}^{\pm y}}=\sqrt{{{y}^{2}}-2c}+y \\

    the first line above is consistent with what i get when i use mathematica

    but after getting p, is it correct to integrate p to get y? It doesn't look correct in my working but I can't find another way to do it.

    i thought about trying to solve the equation as y'= +/- ... instead as a first order ode but it seems too complicated,

    Is there something simple im not seeing?

    Thanks in advance
    Last edited by a moderator: May 5, 2017
  2. jcsd
  3. Mar 30, 2012 #2


    User Avatar
    Science Advisor

    Yes, you are told that p= y'= dy/dx so
    [tex]\frac{dy}{dx}= \pm\frac{1}{\sqrt{y^2- 2c}}[/tex]
    and then
    [tex]\frac{dy}{\pm\sqrt{y^2- 2c}}= dx[/tex]

    Integrate both sides of that.
  4. Mar 30, 2012 #3
    Hey HallsofIvy

    Thanks for replying,

    Are you sure its not:
    [tex] \pm dy \sqrt{y^2- 2c}= dx[/tex]

    since you take the dx to the right side, and the inverted root onto the left?

    using the initial condition I get c=0 since

    & y'(0)=\pm \frac{1}{\sqrt{{{y}^{2}}(0)-2c}}=\pm \frac{1}{\sqrt{1-2c}}=-1 \\
    & \pm \frac{1}{\sqrt{1-2c}}=-1,\,\,\,\pm 1=-\sqrt{1-2c}\,\,squaring\,\,both\,\,sides \\
    & 1=1-2c \\
    & c=0 \\
    & So\,y'(x)=\pm \frac{1}{y} \\
    & \pm ydy=dx \\
    & \pm \frac{1}{2}{{y}^{2}}=x+c \\
    & \pm \frac{1}{2}{{y}^{2}}(0)=\pm \frac{1}{2}=c \\
    & \therefore y(x)=\sqrt{2x\pm \frac{1}{2}} \\

    does that look ok?
    Last edited: Mar 30, 2012
  5. Mar 31, 2012 #4
    I tried it again today with a fresh start and I ended up getting the same thing,
    The thing that makes me sus about it is the +/- inside the square root
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook